2024
DOI: 10.1037/tra0001430
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement desensitization reprocessing as a treatment for PTSD in conflict-affected areas.

Abstract: Objective: One recommended psychological intervention for trauma treatment in Western countries, including posttraumatic stress disorder (PTSD), is eye movement desensitization reprocessing (EMDR). However, there is a paucity of data regarding treatment interventions in low-and middle-income countries. This study examined the efficacy of EMDR for treating posttraumatic stress (PTS), anxiety, and depression among a cohort of individuals with low socioeconomic status in a conflict-affected middle-income country … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Reviews suggest that most EMDR trial participants, at least in studies conducted in the United States, are White, middle‐class, heterosexual, educated, and verbal adults (Madnick & Spokas., 2022). When studies have focused on applications of EMDR for treatment in non‐White participants, the therapy has often been delivered in a Westernized setting or the cohort sample size has been small (Wippich et al., 2023). Most studies also include participants with posttraumatic stress symptoms identified using self‐report instruments rather than clinician‐rated measures, and often, participants do not necessarily meet the full PTSD diagnostic criteria.…”
Section: Cross‐cultural Applications Of Emdr Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews suggest that most EMDR trial participants, at least in studies conducted in the United States, are White, middle‐class, heterosexual, educated, and verbal adults (Madnick & Spokas., 2022). When studies have focused on applications of EMDR for treatment in non‐White participants, the therapy has often been delivered in a Westernized setting or the cohort sample size has been small (Wippich et al., 2023). Most studies also include participants with posttraumatic stress symptoms identified using self‐report instruments rather than clinician‐rated measures, and often, participants do not necessarily meet the full PTSD diagnostic criteria.…”
Section: Cross‐cultural Applications Of Emdr Therapymentioning
confidence: 99%
“…In the largest study to date, 268 adults with low socioeconomic status living in Lebanon, including a small refugee cohort, were treated with individual EMDR for symptoms stemming from a wide range of traumatic events. EMDR was found to be highly effective in reducing posttraumatic stress, depressive, and anxiety symptoms, and results were maintained at 6‐month follow‐up, although there was a 22% dropout rate (Wippich et al, 2023). The authors suggest this may have been a result of the fluidity and social instability of participants’ circumstances.…”
Section: Cross‐cultural Applications Of Emdr Therapymentioning
confidence: 99%
“…EMDR therapy is an empirically supported treatment for psychological trauma, endorsed by the World Health Organisation (2013), United Nations High Commission for Refugees (2022) and the International Society for Traumatic Stress Studies (2019). It is a psychological treatment for pathogenic (trauma) memories and their associated stress symptoms using a model of pathogenesis and change known as adaptive information processing (Hase et al, 2017;Hase, 2021;Farrell et al, 2022;Laliotis and Shapiro, 2022;Wippich et al, 2023). Shapiro (2017) considers EMDR to desensitize disturbing memories and stimulates the reprocessing of associated thoughts, feelings, and sensations towards adaptive resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the epidemiology of SUDs and MHDs among forced migrants from the MENAT region is crucial due to their unique challenges and vulnerabilities. There is a substantial body of research on SUDs [16,17] and especially MHDs [18][19][20][21][22] from the MENAT region. However, the availability of systematic reviews that comprehensively collect and analyze this data is limited.…”
Section: Introductionmentioning
confidence: 99%